Efficient metal halide perovskite light-emitting diodes with significantly improved light extraction on nanophotonic substrates - Qianpeng Zhang (Nature Portfolio, 2019)
The rapid development of halide perovskite light-emitting diodes mainly relies on the optimization of the active layer and charge injection layers. Here Zhang et al. incorporate three-dimensional nanophotonic substrates to enhance light out-coupling and achieve high external quantum efficiency of 17.5%.